Analysis of Macroporous Resin Combined Extraction and Purification of Polyphenols from Agrimonia pilosa Ledeb. and Anti-Tumor Effect In Vitro - Zhanghao Mei; Huifen Li; Tingting Li; Huiping Taoli; Linmei Pan (Molecules)
Agrimonia pilosa Ledeb. (APL), a traditional Chinese herb frequently employed by Professor Zhou Zhongying, a master of traditional Chinese medicine, for colorectal cancer treatment, is rich in polyphenols with potential anti-tumor properties. To elucidate its bioactive components, this study developed a two-step purification process combining macroporous resin adsorption and liquid–liquid extraction to enrich polyphenols from APL (APLs). The adsorption/desorption mechanisms of APLs on macroporous resins were systematically investigated through resin screening, adsorption kinetics, and thermodynamics. The Langmuir isotherm model confirmed the adsorption process as spontaneous and exothermic. Pseudo-second-order kinetics effectively described the adsorption behavior of D101 resin. Optimized adsorption and column elution parameters were established, followed by liquid–liquid extraction for further purification. The components were compared and analyzed by ultra-performance liquid chromatography and quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-Zeno-TOF-MS/MS). It was preliminarily identified that 29 polyphenols were mainly concentrated in water-saturated n-butanol (BEA) and ethyl acetate (ECA) extract fractions. Quantitative analysis using ultra-high performance liquid chromatography–triple quadrupole liquid chromatography–mass spectrometry (UHPLC-C-QTRAP-MS/MS) revealed higher contents of catechin (66.67 ± 1.33 ng·mg−1), hyperoside (382.56 ± 3.65 ng·mg−1), and chlorogenic acid (10.60 ± 0.05 ng·mg−1) in BEA compared to ECA (46.00 ± 2.00, 239.40 ± 2.60, and 3.42 ± 0.01 ng·mg−1, respectively). In vitro experiments demonstrated that BEA exhibited superior antiproliferative activity (IC50: 434.5 μg·mL−1) and significantly inhibited CT26 tumor cell migration compared to ECA (IC50: 672.5 μg·mL−1). The enhanced biological activity of BEA may be due to its higher polyphenol content, suggesting that these compounds mediate their anti-tumor effects through different biochemical pathways. This work lays the foundation for exploring the multi-target mechanism of anti-tumor effects of APLs.